Trauma and Defense Mechanisms in Zach Braff’s Garden State: A Psychoanalytic Analysis (PANOPTICON: Journal of English Studies, 2025)
This study examines the representation of trauma and defense mechanisms in Zach Braff’s Garden State (2004), focusing on the psychological development of the protagonist, Andrew Largeman. The research investigates how unresolved childhood experiences and strained familial relationships shape Andrew’s emotional detachment and his eventual movement toward self-understanding. Drawing on Sigmund Freud’s psychoanalytic theory and Anna Freud’s conceptualization of defense mechanisms, this study analyzes selected scenes using a qualitative film-analysis approach that integrates narrative interpretation with cinematographic observation. The findings reveal that Andrew’s trauma is articulated through consistent patterns of emotional suppression and dissociation, which manifest in three primary defense mechanisms: repression, projection, and sublimation. These mechanisms function as psychological strategies that both conceal and expose the depth of Andrew’s unresolved guilt and inner conflict. The study demonstrates that Garden State portrays trauma not merely as a personal burden but as a psychological process that requires confrontation, emotional openness, and relational support to achieve healing.